Perancangan Interior Surabaya Animal (Dog) Care Community - Susanto, Merliana Megawati (Intra, 2017)
Lack of caring and human responsibility causes many dogs to be stranded on the road. There is a community where they do the rescue and help the dog to find his new family. "Interior Design Surabaya Animal (Dog) Care Community" is facilitating and facilitate rescue activities of the community. Design method used in the form of design stage include; Empathize, define, ideate, prototype, test, and implementation. Concepts raised based on the environment to overcome the problems posed by dogs such as smells, noise, clawing behavior and biting objects around it. While the style of modern design is selected as a support for solving the main problem. Design is classified into 3 areas, namely dog area, service area, and support area. Overall, this design is openly designed with materials, coloring, shape and circulation designed for inner activity A space is warm and familial.